2021
DOI: 10.1002/aenm.202003752
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsically Nonflammable Ionic Liquid‐Based Localized Highly Concentrated Electrolytes Enable High‐Performance Li‐Metal Batteries

Abstract: Research data are not shared.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
115
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(119 citation statements)
references
References 41 publications
1
115
0
Order By: Relevance
“…Basile et al investigated Li deposition in several kinds of ionic-liquid-based electrolytes for Li-metal batteries.Along cycle stability over 5000 ho fL i k Li symmetry was achieved in 1M LiAsF 6 [C3mPyr + ][FSI -] electrolytes. [127] Unfortunately,t he high viscosity and low ionic conductivity of the of ionic liquids at room temperature hinder its practical applications.A saresult, the specific capacity of Li k LiFePO 4 full cells is only 80 mAh g À1 with 1M LiAsF 6 [C3mPyr + ][FSI -]e lectrolytes.H ence,s ome co-solvents such as DOL/DME [125,128] or HFE [129] are added to the ionic liquid to decrease the viscosity.W ang et al demonstrated the synergic effect of LiNO 3 and an ionic liquid to suppress the dissolution of polysulfides (Figure 10 A). [125] Guo et al reported 2M LiTFSI PP13TFSI/DOL/DME(1:1:1) as the electrolyte for Li-metal batteries with ahigh CE of 98 % (Figure 10 B).…”
Section: Ionic-liquid-based Electrolytesmentioning
confidence: 99%
See 1 more Smart Citation
“…Basile et al investigated Li deposition in several kinds of ionic-liquid-based electrolytes for Li-metal batteries.Along cycle stability over 5000 ho fL i k Li symmetry was achieved in 1M LiAsF 6 [C3mPyr + ][FSI -] electrolytes. [127] Unfortunately,t he high viscosity and low ionic conductivity of the of ionic liquids at room temperature hinder its practical applications.A saresult, the specific capacity of Li k LiFePO 4 full cells is only 80 mAh g À1 with 1M LiAsF 6 [C3mPyr + ][FSI -]e lectrolytes.H ence,s ome co-solvents such as DOL/DME [125,128] or HFE [129] are added to the ionic liquid to decrease the viscosity.W ang et al demonstrated the synergic effect of LiNO 3 and an ionic liquid to suppress the dissolution of polysulfides (Figure 10 A). [125] Guo et al reported 2M LiTFSI PP13TFSI/DOL/DME(1:1:1) as the electrolyte for Li-metal batteries with ahigh CE of 98 % (Figure 10 B).…”
Section: Ionic-liquid-based Electrolytesmentioning
confidence: 99%
“…[128] Xu et al employed HFE as diluent for an ionic-liquid-based electrolyte to form LHCE. [129] Some novel ionic liquids have been also proposed for Limetal batteries.Dai et al reported aNa-chelated ionic liquid for Li-metal batteries (Figure 10 C). [130] After Na chelation, the viscosity of the ionic liquid decreased.…”
Section: Ionic-liquid-based Electrolytesmentioning
confidence: 99%
“…As a result, the specific capacity of Li∥LiFePO 4 full cells is only 80 mAh g −1 with 1 M LiAsF 6 [C3mPyr + ][FSI ‐ ] electrolytes. Hence, some co‐solvents such as DOL/DME [125, 128] or HFE [129] are added to the ionic liquid to decrease the viscosity. Wang et al.…”
Section: Electrolyte Design For Practical Li‐metal Batteriesmentioning
confidence: 99%
“…Numerous methods have been proposed to address these problems including electrolyte additives, [34][35][36][37][38][39][40][41][42][43][44][45] artificial SEI, [46][47][48][49][50][51][52][53][54][55][56] superconcentrated electrolyte, [57][58][59][60][61][62][63][64][65][66][67][68][69][70] solid-state electrolyte (SSE), [71][72][73][74][75][76][77][78][79][80] functional membrane, [81][82][83][84]…”
Section: Introductionmentioning
confidence: 99%